Roman imperialism and local identities - Revell, Louise, 19??- (New York)
xvi, 222 sayfa
Keywords: “Revell examines questions of Roman ethnic identity and explores Roman imperialism as a lived experience based around the paradox of similarity and difference. Her case studies of public architecture provide an understanding of how urbanism, the emperor and religion were part of the daily encounters of these communities.” --